2014
DOI: 10.12693/aphyspola.125.449
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation and Fabrication Works on Optimization of High Pressure Aluminum Die Casting Part

Abstract: High-pressure die casting oers reduced costs due to its small tolerances and smooth surface nish. Casting parts produced are consumed by the automotive industry in millions. In this study, the use of computer aided engineering applications on design of high-pressure die-casting was studied. The inuence of casting process steps in die design was studied and analyzed. The casting simulation software was used to improve design and solve problems. By using the simulation software in analyses of die design, the nal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…These systems can be used both as a vent and as a vacuum valve. Wang's study showed that [8][9][10], 3D venting systems, when used as a vent, is more efficient than a conventional chill vent which connected to a vacuum system, and can achieve nearly the same evacuation efficiency as the best available from a simple vacuum system. In another study, Wang et al [8] showed that 3D venting systems, when used in the die casting process, then the machine downtime which is caused by vacuum defects has been reduced.…”
Section: Introductionmentioning
confidence: 99%
“…These systems can be used both as a vent and as a vacuum valve. Wang's study showed that [8][9][10], 3D venting systems, when used as a vent, is more efficient than a conventional chill vent which connected to a vacuum system, and can achieve nearly the same evacuation efficiency as the best available from a simple vacuum system. In another study, Wang et al [8] showed that 3D venting systems, when used in the die casting process, then the machine downtime which is caused by vacuum defects has been reduced.…”
Section: Introductionmentioning
confidence: 99%